1993
DOI: 10.21236/ada264860
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for the Horn of Africa

Abstract: it hu bown deemed by be appeopghate alhey swime at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, over the last twenty years, it has been observed that beyond the Counterterrorism (COT) objective, the primary reasons for the US military's presence in Djibouti have been motivated and driven by its geostrategic position and subsequent geopolitical interests of America. According to Kimani (1993), these interests include guaranteeing and monitoring logistical aid for Gulf wars and safeguarding the Bab al-Mandab Strait which is a crucial shipping route in the region and one of the world's busiest waterways. In addition to these, Sun & Zoubir (2016) buttressed that promoting stability in the Horn of Africa, providing humanitarian assistance, and implementing antipiracy measures are among the activities of America's camp lemonier in Djibouti.…”
Section: Geostrategic Locations Of Fmbs In Djibouti and Economic Inte...mentioning
confidence: 99%
“…However, over the last twenty years, it has been observed that beyond the Counterterrorism (COT) objective, the primary reasons for the US military's presence in Djibouti have been motivated and driven by its geostrategic position and subsequent geopolitical interests of America. According to Kimani (1993), these interests include guaranteeing and monitoring logistical aid for Gulf wars and safeguarding the Bab al-Mandab Strait which is a crucial shipping route in the region and one of the world's busiest waterways. In addition to these, Sun & Zoubir (2016) buttressed that promoting stability in the Horn of Africa, providing humanitarian assistance, and implementing antipiracy measures are among the activities of America's camp lemonier in Djibouti.…”
Section: Geostrategic Locations Of Fmbs In Djibouti and Economic Inte...mentioning
confidence: 99%